2016
DOI: 10.1021/acsami.6b09604
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cellular Internalization and On-Demand Intracellular Release of Doxorubicin by Stepwise pH-/Reduction-Responsive Nanoparticles

Abstract: The efficient delivery of antitumor agents to tumor sites faces numerous obstacles, such as poor cellular uptake and slow intracellular drug release. In this regard, smart nanoparticles (NPs) that respond to the unique microenvironment of tumor tissues have been widely used for drug delivery. In this study, novel charge-reversal and reduction-responsive histidine-grafted chitosan-lipoic acid NPs (HCSL-NPs) were selected for efficient therapy of breast cancer by enhancing cell internalization and intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Thereafter, an equal amount of EDC and NHS (0.05 g) were added to the solution of LA (0.05 g) in ethanol under stirring at 45 • C for 15 min. The amide bonds were formed after addition of CS solution into the LA solution under stirring at 45 • C for 12 h. Afterwards, dialysis tube (12 kDa MWCO) was utilized for 24 h against dH 2 O and finally the freeze-dried NPs were obtained [20].…”
Section: Synthesis Of the Chitosan-lipoic Acid Nanoparticles (Csla-nps)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, an equal amount of EDC and NHS (0.05 g) were added to the solution of LA (0.05 g) in ethanol under stirring at 45 • C for 15 min. The amide bonds were formed after addition of CS solution into the LA solution under stirring at 45 • C for 12 h. Afterwards, dialysis tube (12 kDa MWCO) was utilized for 24 h against dH 2 O and finally the freeze-dried NPs were obtained [20].…”
Section: Synthesis Of the Chitosan-lipoic Acid Nanoparticles (Csla-nps)mentioning
confidence: 99%
“…[18,19]. Thereafter, MT was encapsulated into the hydrophobic core of the nanoparticle containing a disulfide bond of Lipoic acid (LA) utilized as a reduction part [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, stimuli-responsive micelles have been developed to trigger rapid and complete drug release in tumor cells according to the unique physiological conditions of the tumor microenvironment. 36,37 It is generally known that the concentration of glutathione (GSH) in the tumor intracellular milieu is much higher than that of the extracellular milieu. 38 This redox-heterogeneous environment provides the basis of on-demand drug release at tumor sites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that charged-conversional NPs gained satisfactory balance between targeting efficiency and cellular uptake. [11][12][13] Slow and incomplete drug release within tumor cells is another challenge for efficient delivery of antitumor agents since most antitumor drugs achieve their therapeutic effects by reacting with nuclei or organelles.…”
Section: Introductionmentioning
confidence: 99%